Methodological approach for developing online courses: a case study - Irina V. Sitak; Kateryna V. Vlasenko; Oksana M. Kondratyeva; Iryna V. Lovianova; Olena O. Chumak (Academy of Cognitive and Natural Sciences, 2023)
Online courses are becoming more popular and accessible, but they require careful design and development of their structure and content. This paper presents a methodological approach for creating online courses by analysing existing practices and learner feedback. The paper focuses on the case study of the online course "Methods for Teaching Mathematics to Students in Technical Universities", developed and tested by the authors. The paper discusses the main aspects of online course development, such as weekly planning, testing subsystem, video and PDF content, forum and survey subsystems, and assessment of learning outcomes. The paper also evaluates the quality of the online course and identifies some areas for improvement. The paper concludes that online course quality depends on various factors and provides recommendations for online course developers.